Electrical stimulation in upper limb assistance: opportunities and challenges - Routledge, Nathan; Zhang, Dingguo; Metcalfe, Benjamin (Frontiers in Neuroscience, 2026)
The global rise in non-communicable diseases, alongside an aging population, is expected to increase the prevalence of motor impairments and, therefore, the need for assistive care. Upper limb impairments can significantly affect independent living and increase long-term care costs. Wearable assistive devices incorporating electrical stimulation (ES) offer a promising solution to support independence and help alleviate pressures on both formal and informal care provision. The development of hybrid systems, which integrate aspects of robotics and electrical stimulation, aim to overcome the limitations associated with single-modality devices. However, there is limited information on the most appropriate electrical stimulation protocols to use, or on what challenges may be faced in doing so. Correspondingly, this narrative review addresses this gap through assessing the role of electrical stimulation in upper limb assistive technology. By evaluating user requirements and identifying challenges with current stimulation strategies, this review highlights the potential benefits of exploring alternative protocols, beyond conventional functional electrical stimulation (FES) techniques, for upper limb assistance. In particular, addressing practical difficulties of stimulation is likely to be critical for successful user uptake and minimizing device abandonment. The paper subsequently reviews several stimulation strategies which may offer novel research directions and opportunities in the development of upper limb assistive technologies.